2001
DOI: 10.1007/pl00007384
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting effects of acute and chronic dietary exposure to 2-amino-3-methyl-imidazo[4,5-f]quinoline (IQ) on xenobiotic metabolising enzymes in the male Fischer 344 Rat: implications for chemoprevention studies

Abstract: The changes after acute exposure suggest an interaction through the Ah receptor and xenobiotic response element, modified by the glucocorticoid response element. In contrast, the pattern of effects after chronic exposure suggests activation of the antioxidant response element (ARE). Although the acute model is more practically convenient for short-term chemoprevention screening, the data suggest that an entirely new mechanism is being invoked that completely masks effects of the ARE that occur during chronic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…In a study by McPherson et al. ( 47 ) , no significant induction in mRNA expression level or activity of either CYP1A1 or CYP1A2 were reported in the livers of rats receiving 300 p.p.m. IQ in the diet for 52 weeks, but these enzymes were significantly increased after daily administration of 20 mg/kg b.w.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In a study by McPherson et al. ( 47 ) , no significant induction in mRNA expression level or activity of either CYP1A1 or CYP1A2 were reported in the livers of rats receiving 300 p.p.m. IQ in the diet for 52 weeks, but these enzymes were significantly increased after daily administration of 20 mg/kg b.w.…”
Section: Discussionmentioning
confidence: 91%
“…IQ in the diet for 52 weeks. ( 47 ) Significant increases in CYP1A1 expression in the 100 p.p.m. group provide an alternative mechanism that can compensate for decreased CYP1A2 activity.…”
Section: Discussionmentioning
confidence: 99%
“…administration for 52 weeks significantly enhanced GST activity as well as UGT conjugating activity in F344 rats. (37) As mentioned above, GST is known as one of the most inducible prototypical phase II enzymes in the presence of Nrf2. (23) In fact, our data demonstrated that induction of GST activities did not occur following IQ exposure to Nrf 2(-/-) mice in either sex.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, IQ itself is able to affect the activity of P450s enzymes depending on the treatment regimen [40]. Low P450s enzyme activity would delay the metabolic conversion of IQ into a substrate for GST enzymes and this may be one factor in the low mRNA levels of gpx1 after treatment with IQ.…”
Section: Discussionmentioning
confidence: 99%